Curcumin loaded polycaprolactone scaffold capable of anti-inflammation to enhance tracheal cartilage regeneration. (December 2022) - Yang, Minglei; Sun, Weiyan; Wang, Long; Tang, Hai; Xu, Xiang; Yang, Liangwei; Ni, Junjun; Zheng, Kuoen; Jiang, Xu; Xu, Weiwen; Zhao, Guofang; She, Yunlang; et al.
Graphical abstract: Highlights: Cur/PCL scaffold exhibited a favorable anti-inflammation property in vitro . Cur/PCL displayed enhanced stability of cartilaginous phenotype in vivo . Cur/PCL displayed inflammatory-related response in vivo . Cur/PCL inhibited granulation hyperplasia after orthotopic tracheal transplantation. Cur/PCL promote rabbit survive after orthotopic tracheal transplantation. Abstract: An inflammatory reaction is one of the primary reasons for deteriorating tracheal cartilage regeneration in vivo, hindering tracheal defect restoration with prominent fibrosis and granulation hyperplasia. Therefore, effective anti-inflammatory therapeutic strategies may considerably promote tracheal cartilage regeneration and tracheal defect restoration. We prepared a porous ring-shaped Cur/PCL scaffold by loading curcumin (Cur), an anti-inflammatory compound, into polycaprolactone (PCL) using the supercritical CO2 foaming method. Our results confirmed that the Cur/PCL possessed similar porosity with the PCL alone scaffold. The Cur loaded within the Cur/PCL scaffold exhibited sustained release kinetics, stability and a favorable anti-inflammation property in vitro . Moreover, The Cur/PCL scaffold displayed gratifying biocompatibility and supported ring-shaped tracheal cartilage regeneration. In addition, the engineered ring-shaped tracheal cartilage in the Cur/PCL group showed a potent anti-inflammatory effect on maintaining the cartilaginous phenotype and enhanced tracheal cartilage regeneration when subcutaneously implanted into an autologous rabbit. Furthermore, the engineered cartilage in the Cur/PCL group exerted a favorable anti-inflammatory capacity to significantly suppress fibrogenesis and granulation hyperplasia, enhancing tracheal cartilage regeneration and elevating survival rate of experimental rabbits after orthotopic transplantation. This study provides an effective strategy to prepare an anti-inflammatory scaffold for enhancing cartilage regeneration in vivo and repairing tracheal cartilage defects.